Search for a multi-Higgs-boson cascade in W+W -bb̄ events with the ATLAS detector in pp collisions at √s = 8 TeV - Alconada Verzini, María Josefina (2014)
A search is presented for new particles in an extension to the Standard Model that includes a heavy Higgs boson (H0), an intermediate charged Higgs-boson pair (H-), and a light Higgs boson (h0). The analysis searches for events involving the production of a single heavy neutral Higgs boson which decays to the charged Higgs boson and a W boson, where the charged Higgs boson subsequently decays into a W boson and the lightest neutral Higgs boson decaying to a bottom-antibottom-quark pair. Such a cascade results in a W-boson pair and a bottom-antibottom-quark pair in the final state. Events with exactly one lepton, missing transverse momentum, and at least four jets are selected from a data sample corresponding to an integrated luminosity of 20.3 fb-1, collected by the ATLAS detector in proton-proton collisions at √s = 8 TeV at the LHC. The data are found to be consistent with Standard Model predictions, and 95% confidence-level upper limits are set on the product of cross section and branching ratio. These limits range from 0.065 to 43 pb as a function of H0 and H- masses, with mh 0 fixed at 125 GeV.